Classification of strategies for socio-economic development of united territorial communities - Nadiya Pylypiv; Iryna Piatnychuk; Sviatoslav Sologub (Vasyl Stefanyk Precarpathian National University, 2020)
The article deals with the classification of strategies for socio-economic development of united territorial communities in a dynamic business environment. The purpose of the article is to build a classification of strategies for socio-economic development of the united territorial communities to increase the effectiveness of their development and implementation in practice. Based on the conducted research, the author's vision of defining the essence of 'socio-economic development of united territorial communities' was formed. It will contribute to a clearer understanding of this category. We defined the characteristics that determine the socio-economic development of the united territorial community. We evaluated the dynamics of the process of creating territorial communities in Ukraine and identified opportunities for creating new communities. To build a strategy for the socio-economic development of united territorial communities that would meet the requirements of the modern business environment, as well as satisfy the expectations that are set for it, we systemized various types of strategies into classification groups. Among them: development strategies, strategies of management and utilization of united territorial communities resources, gender-oriented strategies, strategies to counter, strategies of the development of the economic sectors, strategies of the development of UTC areas, digitalization strategies, communication and information strategies,  management strategies, European integration strategies. The developed classification of strategies will contribute to a more accurate formation of strategic goals and actions, and contribute to the effective implementation and realization of the developed strategy of united territorial communities. The obtained results of the study serve as the basis for subsequent research in terms of ensuring the socio-economic development of united territorial communities.